TEKNIK PELAPISAN SILIKON DIOKSIDA (SiO2) DENGAN ALAT RF-SPUTTERING ARC-12M - Widodo, Slamet (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2012)
In this paper described the technique of metal and non metal coating (Alloy) by using a sputtering ARC-12M. Sputtering is a process ejected material from a surface of solids or liquids due to ground by high-energy particles up to momentum exchange occurs (momentum exchange). Target in the form of coating material is placed in the same direction with the substrate in a vacuum chamber with initial pressure (base pressure) equal to 5x10-4 to 5x10-7torr. Types of particles that were fired from the gas ions that are not easy to react to other substances or inert gas. On Non-metal deposition process (Alloy) eg Silicon Dioxide (SiO2) by RF-sputtering method, the thickness would increase linearly with increasing time.The deposition of chromium (Cr) with Argon (Ar) gas at a pressure of 15 mTorr, it produce relatively higher than the pressure of 25 mTorr. Keywords :Deposition, SiO2, RF Sputtering ARC-12M.